(untitled) (Revista Espinhaço, 2020)
The knowledge of the floristic composition of the urban tree community helps the formulation of public policies and management decision-making. In this study, we sought to identify the species that comprise the afforestation of Diamantina, MG. Initially, we conducted a selective sampling of the urban area, recording the trees present on sidewalks, central flowerbeds and squares. Then, we calculate the Shannon index to assess the level of floristic diversity. The Shannon index was equal to 3.7, showing high floristic diversity. Most species are of native origin (64.03%) and most (77.83%) are located in the squares. We concluded that afforestation has good floristic diversity and a high frequency of native species, points recommended for urban afforestation. Squares are strategic spaces and should be the focus of public policies. It is recommended to draw up a afforestation plan, which guides and regulates the planting of trees.